Predictors of Handgrip Strength Changes in Elderly Patients - Madina, Ummi Ulfah; Setiati, Siti; Laksmi, Purwita Wijaya; Mansjoer, Arif (UI Scholars Hub, 2021)
Introduction. The increasing elderly population throughout the world has been related to the increased prevalence of sarcopenia and frailty. Handgrip strength is a component of sarcopenia, one of frailty syndrome phenotypes. Previous studies have assessed the association of age, sex, nutritional status, functional status, mental status, and comorbidity, but varied results. No longitudinal study has been done to determine the correlation of handgrip strength changes with age, sex, nutritional status, functional status, mental status, and comorbidity in Indonesia. The aim of this study was to determine the correlation between age, sex, nutritional status, functional status, depressive symptoms, comorbidity, and handgrip strength changes in elderly patients. Methods. A prospective cohort study using secondary data of elderly patients who were routinely visiting Geriatric OutPatients Clinic at Cipto Mangunkusumo Hospital, Jakarta, from the INA-FRAGILE register observed for one year (2013- 2014). The multivariate logistic regression analysis was used to assess the correlation between sex, age, nutritional status (MNA score), functional status (ADL score), depressive symptoms (GDS-SF score), comorbidities (CIRS score), and handgrip strength changes. Results. From 162 subjects which were included in the study, the mean age was 72.9 (SD 5.9) years, predominantly female (57.41%), with good nutrition (83.9%), independent (median 9- 20), not depressed (median 0-11), has average comorbidity index 11.8 (SD 3.7), and 53.1% experienced decreased handgrip strength. Nutritional status (OR = 2.7, p = 0.033) and comorbidity (OR 0.3, p <0.002) correlated with handgrip strength changes